Optimal design of an aeroelastic wing structure with seamless control surfaces - Perera, Melanie; Guo, Shijun J. (Professional Engineering Publishing, 2009)
This article presents an investigation into the concept and optimal design of a lightweight seamless aeroelastic wing (SAW) structure for small air vehicles. Attention has been first focused on the design of a hingeless flexible trailing edge (TE) control surface. Two innovative design features have been created in the SAW TE section: an open sliding TE and a curved beam and disc actuation mechanism. This type of actuated TE section allows for the SAW having a camber change in a desirable shape and minimum control power demand. This design concept has been simulated numerically and demonstrated by a test model. For a small air vehicle of large sweep back wing, it is noted that significant structural weight saving can be achieved. However, further weight saving is mainly restricted by the aeroelastic stability and minimum number of carbon/epoxy plies in a symmetric layup rather than the structural strength. Therefore, subsequent effort was made to optimize the primary wing box structure. The results show that an initial structural weight can be reduced significantly under the strength criterion. The resulting reduction of the wing box stiffness and aeroelastic stability and control effectiveness can be improved by applying the aeroelastic tailoring. Because of the large swept angle and resulting lightweight and highly flexible SAW, geometrical non-linearity and large bending-torsion aeroelastic coupling have been considered in the analysis.
Keywords: Article Subject Terms: Indexing in process